LEARNING INDONESIAN LANGUAGE AND LITERATURE AT MTsN 3 WEST ACEH - AH, Rozita Hasni (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2021)
Learning Indonesian in the 2013 curriculum is text-based. Text is an entire expression of human thought that includes situation and context. The implementation of learning uses a scientific approach with an appropriate model. KD achievement in KI groups 1 and 2 is determined by KD achievement in KI groups 3 and 4. Language should be seen as a text, not merely a collection of words or linguistic rules. Language is functional, meaning that the use of language can never be separated from context because the form of language used reflects the ideas, attitudes, values, and ideologies of the user or users.